Finite Element Analysis of Thermal-structural Coupling for an Aeronautical Spiral Bevel Gear - Yao Huijun; Liu Shijun; Xu Wenbo; Liu Jie; Wang Xiaopeng (Jixie chuandong)
According to the basic theory of heat transfer,gear meshing and tribology,using thermal-structure coupling theory and finite element whole simulation analysis method,the three-dimensional finite element model for a pair of spiral bevel gear in the use of aeronautic is established. The single structure load analysis and the whole thermal-structure coupling analysis are carried out for a group of spiral bevel gear,and the results are compared and analyzed. Finally,the results are comparatively analyzed and verified by using the KISSsoft mechanical transmission design and analysis software. The results show that the maximum contact stress occurs on the meshing surface near the top of tooth,approximately presenting oval-shaped distribution. The maximum contact stress of thermal-structure coupling analysis of gear teeth relative to static contact stress and KISSsoft contact stress have respectively increased 5. 3% and 7. 45% due to the influence of bulk temperature fields,which illustrates the results of the finite element analysis and the results of the KISSsoft analysis are consistency,and then a theoretical basis for the structure optimization and gear modification of the spiral bevel gear pair can be provided.